2020
DOI: 10.7150/jca.47870
|View full text |Cite
|
Sign up to set email alerts
|

PRIM1 promotes the proliferation of hepatocellular carcinoma cells in vitro and in vivo

Abstract: PRIM1 plays an important role during oncogenesis, however it has never been reported in liver cancer, and thus our objective is to explore the role of PRIM1 in liver cancer. We selected RNAseq data of 50 paired liver cancer samples from the Cancer Gene Atlas (TCGA), and then bioinformatics methods and Mann-Whitney U test were used to analyze the correlation between PRIM1 and the clinical pathological stage of liver cancer. Quantitative polymerase chain reaction (QPCR) was used to detect mRNA expression of PRIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In the present study, knockdown of PRIM1 resulted in an increase in Cdc25, Cyclin B, and Cdc2, arresting the cell cycle in G2/M phase, along with a decrease in S-phase cells and an increase in sub-G1 phase cells (apoptotic cells). Knocking down PRIM1 in cancer cell lines increased apoptosis in our and other studies [ 31 , 32 ]. Therefore, our results revealed that PRIM1 was a tumor-promoting regulator that induced the malignant behavior of gastric carcinoma.…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, knockdown of PRIM1 resulted in an increase in Cdc25, Cyclin B, and Cdc2, arresting the cell cycle in G2/M phase, along with a decrease in S-phase cells and an increase in sub-G1 phase cells (apoptotic cells). Knocking down PRIM1 in cancer cell lines increased apoptosis in our and other studies [ 31 , 32 ]. Therefore, our results revealed that PRIM1 was a tumor-promoting regulator that induced the malignant behavior of gastric carcinoma.…”
Section: Discussionsupporting
confidence: 79%
“…PRIM1 containing two subunits synthesizes the RNA primer for the discontinuous DNA replication ( Lee et al, 2019 ). Silencing of PRIM1 gene expression in human hepatic carcinoma cells significantly inhibits the cell proliferation and increases the cell apoptosis ( Jiang et al, 2020 ). The relationship between DNA replication and MCM3 or MCM4 has been described above.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, PRIM1 was also identified as a predictor that indicated poor survival of tumor patients. Though recent studies described the abnormal expression features of PRIM1 [ 15 ], the mechanisms underlying its oncogenic roles have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%